2010
DOI: 10.1086/656587
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Acute Myocardial Infarction and Stroke among Elderly Persons by Dual Pneumococcal and Influenza Vaccination: A Prospective Cohort Study

Abstract: Dual vaccination with PPV and TIV is effective in protecting elderly persons with chronic illness from developing complications from respiratory, cardiovascular, and cerebrovascular diseases, thereby reducing hospitalization, coronary or intensive care admissions, and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 36 publications
3
120
1
1
Order By: Relevance
“…44 However, this study had several limitations, and others have not confirmed this association. 9,12,16,17,45 Thus, we hypothesized that we would not detect an association between pneumococcal vaccination and major adverse vascular events, and if an association was detected, it would likely be due to confounding bias. The model was adjusted for the following covariates: coronary artery disease; diabetes mellitus; hypertension; stroke; admission to a nursing home; use of aspirin, ␤-blockers, lipid-lowering drugs, angiotensin-converting enzyme inhibitors, or angiotensin II inhibitors; and a propensity score for pneumococcal vaccination that included age, sex, body mass index, ethnicity, education, vitamin use, smoking history, alcohol use, and history of influenza vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 However, this study had several limitations, and others have not confirmed this association. 9,12,16,17,45 Thus, we hypothesized that we would not detect an association between pneumococcal vaccination and major adverse vascular events, and if an association was detected, it would likely be due to confounding bias. The model was adjusted for the following covariates: coronary artery disease; diabetes mellitus; hypertension; stroke; admission to a nursing home; use of aspirin, ␤-blockers, lipid-lowering drugs, angiotensin-converting enzyme inhibitors, or angiotensin II inhibitors; and a propensity score for pneumococcal vaccination that included age, sex, body mass index, ethnicity, education, vitamin use, smoking history, alcohol use, and history of influenza vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…1 Observational studies that have evaluated the association between influenza vaccination and major adverse vascular events such as myocardial infarction and stroke have had conflicting results. [7][8][9][10][11][12][13][14][15][16][17] A meta-analysis of 2 small randomized trials showed no significant difference of immunization in preventing acute myocardial infarction or cardiac death, although point estimates of effect tended toward protection and a recent small open-label randomized trial showed a reduction in major adverse vascular events in influenza-vaccinated patients with a history of acute coronary syndrome. 1,18 -21 We sought to determine whether influenza vaccination was associated with a reduction in major adverse vascular events using a large clinical database consisting of prospectively collected data from the Ongoing Telmisartan Alone and in Combination With Ramipril Global EndPoint Trial (ONTARGET) and the Telmisartan Randomized Assessment Study in ACE Intolerant Subjects with Cardiovascular Disease (TRANSCEND) trials.…”
Section: Clinical Perspective On P 286mentioning
confidence: 99%
“…Immunization of apoE -/-mice with PC-keyhole limpet hemocyanin (KLH)-conjugate coupled to unmethylated cytosine-guanine dinucleotides (CpG) oligonucleotides as adjuvant significantly increased IgG and IgM levels against PC and oxLDL, with reduced macrophage oxLDL uptake, and reduced atherosclerosis. 33 However, using myocardial infarction or stroke as endpoints, observational cohort studies in humans did not show consistent protective effects of pneumococcal vaccines, [34][35][36][37] leaving the question of whether active immunization against PC will reduce atherosclerosis in humans unanswered.…”
Section: Other Lipid-related Antigensmentioning
confidence: 99%
“…Also, there is an association between respiratory infections and increased risk of cardiac ischemia 80.81 (B) and strokes 82 (B). These two vaccinations reduce respiratory infections, hospitalizations and acute cardiovascular events 63 (B).…”
Section: (B)mentioning
confidence: 99%